Apperceptive defects in accounting information system - Vysochan, O.; Vysochan, O. (Lviv Politechnic Publishing House, 2018)
The article is concerned with a relevant issue oforigin and adverse effects caused by defects of accounting and information system. The aim is the research and categorization of defects related to the perception of accounting information by recipients and the influence of such defects on efficiency of decision-making. Interdependence between the part of information unperceived by the consumer because of defects and coefficient of accounting information perception has been determined in this work. The work is also concerned with the classification of defects that may arise in accounting and information system of economic entities and stem from one of the reasons caused by other information system constituents or their combination: peculiarities (including psychological, medical and biological ones) of the recipient; characteristics of accounting information source; transit properties of transmitting medium; qualitative, quantitative, value and formal properties of accounting information. Factors affecting apperception of accounting information by the consumer have been characterized. Three types of complex apperceptive defects arising as a result of various impact factors combination have been pointed out and specified: type I – due solely to internal factors; transmitting medium, accounting information and its source are not involved in their generation; type II – arise in the course of processing information by the person concerned though their reasons are external; type III – combine characteristics of the first type (source of origin, accounting information, its generator and/or transmitting medium) and the second type (primary cause: internal characteristics of the recipient). It has been concluded that apperceptive defects influence accounting system of economic entity, and they are one of the reasons leading to aberration of accounting and information flows.
Keywords: accounting information; recipient; information source; transmitting medium; accounting system; apperception of information; 657.01; 316.776; 159.937